Anxiety: phenomenology, epidemiology, and risk factors during the novel coronavirus SARS-CoV-2 (COVID-19) pandemic - A. G. Merkin; S. S. Akinfieva; A. V. Martyushev-Poklad; O. P. Beloskurskaya; E. N. Dinov; S. L. Ostrovsky; A. N. Komarov; O. Yu. Zakharova; V. A. Kazhin; I. A. Nikiforov; M. Glover (Неврология, нейропсихиатрия, психосоматика)
The COVID-19 coronavirus pandemic in 2020 led to significant negative social consequences associated inter alia with adverse effects on mental health. One of the most common mental illness is anxiety disorders, the rise in which is characteristic of social upheaval periods. This paper analyzes the problem of anxiety, reviews information on the epidemiology of anxiety, on the factors and mechanisms of its development. It unveils the association of anxiety with addictive disorders, lifestyle factors, and traumatic childhood experience and highlights the problem of increased anxiety in the context of the novel coronavirus COVID-19 pandemics in Russia.